Extracellular polysaccharide-facilitated selenium nanoparticle assembly and metabolic reprogramming support efficient selenite biotransformation by ARTP-mutagenized Lactiplantibacillus plantarum Vse252 - Lihui Tan; Xinyan Wang; Lin Hu; Xiang Gen; Shirui Yu; Xue Li; Xinyu Yan; Bo He; Jun Zhang; Yongzhong Wang; Hengqian Lu (Bioresource Technology, 2026)

Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

A Pt/h-Co-Nc nanozyme hydrogel air-fuel cell mediating cascade DNA walking for point-of-care detection - Ning Li; Lin Sun; Kaili Wang; Lihui Mao; Xuecai Tan; Haibo Wang; Ke-Jing Huang; Shaogang Liu (Chemical Engineering Journal, 2026)

Charged cellulose-inserted-nonwoven fabric composite membrane for selective Mg2+/Li+ separation - Yingchao Wang; Zhen Wang; Qiyang Lu; Qingxian Miao; Yonghao Ni; Liulian Huang; Lihui Chen; Zhiwei Lin; Yuxin Liu; Jianguo Li (Chemical Engineering Journal, 2026)

Agmatine induces mitophagy via the PTS-I2R pathway to increase autophagic flux and attenuate sepsis-induced intestinal epithelial cell apoptosis - He Jin; Shuangqin Yin; Yongming Li; Xiangwei Hou; Lin Qiao; Tianyin Kuang; Jing Zhou; Xue Yang; Wanting Zeng; Chao Fan; Li Luo; Lihui Wang; et al. (Inflammation Research, 2026)

Cooling history and source characteristics of the Chang'e-6 low-Ti basalt: Constraints from plagioclase - Di Zhang; Wei Yang; Huijuan Zhang; Honggang Zhu; Yunhong Fan; Hengci Tian; Shitou Wu; Lihui Jia; Lixin Gu; Yangting Lin (Icarus, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Identification and validation of a QTL, QSNS.caas-3D.1, for spikelet number per spike in wheat - Xuezhong Liang; Junli Yang; Ze Liu; Fuping Zhang; Haiming Han; Shenghui Zhou; Jinpeng Zhang; Bing Han; Yida Lin; Hong-Qing Ling; Li Zheng; Junbo Yang; et al. (Theoretical and Applied Genetics, 2026)

Chicken sternum cartilage protein-chelated calcium: enhance bone density in vivo and in vitro, with insights into chelation mechanism - Shikun Suo; Yanli Wang; Lihui Du; Maolin Tu; Kuo Dang; Jingyi Chen; Yi Lin; Yali Dang; Qingqing Li (Food Research International, 2026)

Delivery of carbonaceous materials to the Moon - Linxi Li; Mengfan Qiu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Yuyang He; Shitou Wu; Hao Wang; Guoqiang Tang; Di Zhang; et al. (Icarus, 2026)

Maillard-induced pea protein isolate/carboxymethyl chitosan conjugates: Synthesis, characterization, and applications in O/W emulsions - Wenhao Liu; Xiaoye Xu; Kehao Li; Siya Lin; Xinxin Zeng; Lihui Duan; Yan Huang; Shini Ma; Xiaoyan Liu; Yajie Shen; Jie Pang; Chunhua Wu (Food Research International, 2026)

Dihydroartemisinin targets ANXA2 to suppress hepatocellular carcinoma angiogenesis through the PI3K/AKT signaling pathway - Lulu Cao; Lihui Wang; Jun Lin; Jian Zhao; Bolun Xu; Jianxin Chen; Juanjuan Hu; Siwei Wang; Junhua Yu (Tissue and Cell, 2025)

Enhancing separation and anti-fouling performance of cellulose acetate ultrafiltration membranes by introducing natural deep eutectic solvent - Danni Lin; Sisi Hu; Leyuan Zhou; Xiaojuan Ma; Lihui Chen; Dong Wang; Liulian Huang (Journal of Water Process Engineering, 2025)

Effects of ice-binding protein from Leucosporidium sp. AY30 (LeIBP) on physicochemical quality, myofibrillar protein and ice crystal morphology of largemouth bass during air freezing - Junde Ren; Feifei Hu; Farooq Muhammad; Lihui Hu; Tao Song; Maninder Meenu; Jie Lin; Ying Liu; Hosahalli S. Ramaswamy; Yong Yu (Food Research International, 2025)

Regulating the morphological structure of cellulose acetate ultrafiltration membrane by adjusting the ratio of N, N-dimethylacetamide: N-methyl pyrrolidone in co-solvent to enhance separation and anti-fouling performance - Minfu Mo; Yaling Lin; Danni Lin; Xiaojuan Ma; Yubin Hong; Lihui Chen; Dong Wang; Liulian Huang (Desalination, 2025)

Crop sample prediction and early mapping based on historical data: Exploration of an explainable FKAN framework - Feifei Cheng; Bingwen Qiu; Peng Yang; Wenbin Wu; Qiangyi Yu; Jianping Qian; Bingfang Wu; Jin Chen; Xuehong Chen; Francesco N. Tubiello; Piotr Tryjanowski; Viktoria Takacs; et al. (Computers and Electronics in Agriculture, 2025)

Rainfall-driven shifts in eukaryotic microbial communities: Enhanced stochasticity and altered co-occurrence networks in the Fen River - Lihui Liu; Lin Zhang; Ruikai Zhang; Shulian Xie; Fangru Nan; Yang Liu (Limnologica, 2025)

The role of atmospheric volatile organic compounds (VOCs) in ozone formation around China's largest plywood manufacturer - Ningjie Li; Ting Sun; Stephen Mudge; Yuanxun Zhang; Zhenhui Gao; Lihui Huang; Jianing Lin (Environmental Pollution, 2025)

Corrigendum to “Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils” [Icarus 429 (2025) 116448] - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

The effect of ice-binding protein from Leucosporidium sp. AY30 (LeIBP) on physicochemical quality and microstructure of largemouth bass during frozen storage - Junde Ren; Feifei Hu; Maninder Meenu; Lihui Hu; Yuxiao Mao; Tao Song; Jie Lin; Ying Liu; Hosahalli S. Ramaswamy; Yong Yu (Innovative Food Science & Emerging Technologies, 2025)

High electrocatalytic activity of crystallization-modulated ordered PtCu3/C nanoalloy catalysts for oxygen reduction reaction - Xiaomei Li; Linfeng Fu; Lin Cao; Lihui Lei; Xinxing Zhan; Changgang Hu; Xin Tong; Juan Tian (Chemical Engineering Journal, 2025)

The Proteomic Analysis of Chronic Migraine Exosomes Reveals Disease Patterns and Potential Biomarkers - Weiyun Zhang; Fen Wan; Lihui Duan; Wen Tao; Jun Wang; Lin Huang; Lanyun Yan (Molecular Neurobiology, 2025)

Inactivated LMBV vaccine with nano‑aluminum adjuvant provided immune protection in largemouth bass (Micropterus Salmoides) - Xia Luo; Ruoxuan Wang; Baofu Ma; Ouqin Chang; Xiaozhe Fu; Hongru Liang; Yinjie Niu; Qiang Lin; Lihui Liu; Aijun Lv; Ningqiu Li (Aquaculture, 2025)

Modulating charge transfer and constructing synergistic bimetallic active sites for CO-SCR reactions in inverse spinel - Qin Li; Xiaorong Han; Lin Tao; Qiuju Qin; Xuechi Du; Yuzhu Liang; Bin Li; Zhengjun Chen; Liya Zhou; Lihui Dong (Journal of Environmental Chemical Engineering, 2024)

Metabolic changes related to the Maillard reaction in rice yellowing induced by fungal infection: A study based on untargeted metabolomics analysis - Yunjing Zhou; Xiaolu Chen; Yao Lei; Lin Tao; Yong Li; Fei Shen; Lihui Du (Food Bioscience, 2024)

KMT2D deficiency leads to cellular developmental disorders and enhancer dysregulation in neural-crest-containing brain organoids - Ziyun Shan; Yingying Zhao; Xiuyu Chen; Guodong Zhan; Junju Huang; Xuejie Yang; Chongshen Xu; Ning Guo; Zhi Xiong; Fang Wu; Yujian Liu; He Liu; et al. (Science Bulletin, 2024)

Acid-assisted pretreatment for sweet elephant grass in choline chloride/glycerol DES: Experimental and mechanism study - Yining Zhang; Weizhen Xie; Weidong Li; Yue Tang; Jiali Wu; Lihui Gan; Ling-Ping Xiao; Xu Zhang; Lu Lin; Xing Tang (Chemical Engineering Journal, 2024)

Map-based cloning of LPD, a major gene positively regulates leaf prickle development in eggplant - Changjiao Ke; Wenxiang Guan; Jialong Jiang; Likun Huang; Hui Li; Wenjing Li; Yanyu Lin; Lihui Lin; Xiaofang Xie; Weiren Wu; Wenxia Gao; Yan Zheng (Theoretical and Applied Genetics, 2024)

BMSC-Derived Exosomes Carrying miR-26a-5p Ameliorate Spinal Cord Injury via Negatively Regulating EZH2 and Activating the BDNF-TrkB-CREB Signaling - Min Chen; Yu Lin; Wenbin Guo; Lihui Chen (Molecular Neurobiology, 2024)

Biomimetic cellulose membrane enables high-performance salinity gradient energy conversion: Coupling surface charge and nanopore structure - Jianping Shi; Kairui Lin; Yuanyuan Liu; Shengyue Niu; Yu Zhang; Weikai Yang; Liulian Huang; Jianguo Li; Lihui Chen (Chemical Engineering Journal, 2024)

Thermostatic microwave-assisted pretreatment of corn stover at atmospheric pressure to enhance saccharification - Lihong Wang; Jinghua Fan; Lihui Gan; Xianhai Zeng; Lu Lin; Jian Liu (Biomass and Bioenergy, 2024)

Positive contributions of the stem to the formation of white tea quality-related metabolites during withering - Lihui Xiang; Chen Zhu; Jiajia Qian; Xiaochen Zhou; Miao Wang; Zhenshuo Song; Changsong Chen; Wenquan Yu; Lin Chen; Lanting Zeng (Food Chemistry, 2024)

Tissue factor pathway inhibitors disrupt structures of rhabdovirus/ranairidovirus and inhibit viral infection in Chinese perch, Siniperca chuatsi - Baofu Ma; Jingkang Li; Min Zhang; Xiaozhe Fu; Hongru Liang; Yinjie Niu; Qiang Lin; Xia Luo; Lihui Liu; Jianguo Su; Jin Zhou; Ningqiu Li (Fish & Shellfish Immunology, 2024)

PLD2 deletion ameliorates sepsis-induced cardiomyopathy by suppressing cardiomyocyte pyroptosis via the NLRP3/caspase 1/GSDMD pathway - Jun Li; Da Teng; Wenjuan Jia; Lei Gong; Haibin Dong; Chunxiao Wang; Lihui Zhang; Bowen Xu; Wenlong Wang; Lin Zhong; Jianxun Wang; Jun Yang (Inflammation Research, 2024)
Objective Sepsis-induced cardiomyopathy (SICM) is a life-threatening complication. Phospholipase D2 (PLD2) is crucial in mediating inflammatory reactions and is associated with the prognosis of patients with sepsis. Whether PLD2 is involved in the pathophysiology of SICM remains unknown. This study aimed to investigate the effect of PLD2 knockout on SICM and to explore potential mechanisms. Methods The SICM model was established using cecal ligation and puncture in wild-type and PLD2-knockout mice and lipopolysaccharide (LPS)-induced H9C2 cardiomyocytes. Transfection with PLD2-shRNA lentivirus and a PLD2 overexpression plasmid were used to interfere with PLD2 expression in H9C2 cells. Cardiac pathological alterations, cardiac function, markers of myocardial injury, and inflammatory factors were used to evaluate the SICM model. The expression of pyroptosis-related proteins (NLRP3, cleaved caspase 1, and GSDMD-N) was assessed using western blotting, immunofluorescence, and immunohistochemistry. Results SICM mice had myocardial tissue damage, increased inflammatory response, and impaired heart function, accompanied by elevated PLD2 expression. PLD2 deletion improved cardiac histological changes, mitigated cTNI production, and enhanced the survival of the SICM mice. Compared with controls, PLD2-knockdown H9C2 exhibits a decrease in inflammatory markers and lactate dehydrogenase production, and scanning electron microscopy results suggest that pyroptosis may be involved. The overexpression of PLD2 increased the expression of NLRP3 in cardiomyocytes. In addition, PLD2 deletion decreased the expression of pyroptosis-related proteins in SICM mice and LPS-induced H9C2 cells. Conclusion PLD2 deletion is involved in SICM pathogenesis and is associated with the inhibition of the myocardial inflammatory response and pyroptosis through the NLRP3/caspase 1/GSDMD pathway.

Post-disaster spatial reconstruction from the perspective of a rural settlement niche in the upper reaches of the Minjiang River - Yanguo Liu; Li Wang; Qiang Zou; Jingji Li; Yafeng Lu; Lin Li; Binni Xu; Lihui Wang (Journal of Mountain Science, 2024)

N-S variations of crustal structure beneath the central Tarim Basin from joint inversion of receiver functions, ambient seismic noise surface wave dispersion, and magnetotelluric data - Miao Peng; Handong Tan; Changhong Lin; Shaoqian Hu; Pingping Wu; Lehong Xu; Chonglong Wang; Yifan Liu; Lihui Wang; Bohao Li (Tectonophysics, 2024)

Chromosomal mapping of a major genetic locus from Agropyron cristatum chromosome 6P that influences grain number and spikelet number in wheat - Yida Lin; Shenghui Zhou; Wenjing Yang; Bing Han; Xuezhong Liang; Yuxin Zhang; Jinpeng Zhang; Haiming Han; Baojin Guo; Weihua Liu; Xinming Yang; Xiuquan Li; et al. (Theoretical and Applied Genetics, 2024)

In vivo and in vitro, antiviral effects of two mixture of Chinese herbal drug active monomers against MSRV and LMBV in largemouth bass (Micropterus salmoides) - Yinjie Niu; Xiaozhe Fu; Qiang Lin; Hongru Liang; Xia Luo; Shaozhi Zuo; Lihui Liu; Ningqiu Li (Aquaculture, 2023)

N-doped porous carbon material derived by MOFs calcined in proper oxygen atmosphere as high-performance catalyst for the low-temperature NH3-SCR - Jiexuan Zhu; Donghai Mo; Lin Tao; Jinfeng Li; Shiying Fu; Lihui Dong; Bin Li; Zhengjun Chen; Minguang Fan (Journal of Environmental Chemical Engineering, 2023)

Association of time spent in outdoor light and genetic susceptibility with the risk of type 2 diabetes - Jing Lin; Hongxi Yang; Yuan Zhang; Lihui Zhou; Yanchun Chen; Weili Xu; Yaogang Wang (Science of The Total Environment, 2023)

Consistent differences in brain structure and functional connectivity in high-altitude native Tibetans and immigrants - Xinjuan Zhang; Weiwei Xie; Wenrui Du; Yanqiu Liu; Jianzhong Lin; Wu Yin; Lihui Yang; Fengjuan Yuan; Ran Zhang; Haipeng Liu; Hailin Ma; Jiaxing Zhang (Brain Imaging and Behavior, 2023)

Spatial multi-omics co-sequencing provides new opportunity for in situ transcriptional regulation study - Lihui Lin; Quanyou Cai; Jiekai Chen (Science Bulletin, 2023)

Ceria-Promoted and stabilized copper and iron oxides cooperatively catalyze NO efficient degradation by CO - Xiaobing Shi; Lin Tao; Zhangfa Tong; Minguang Fan; Lihui Dong; Bin Li (Fuel, 2023)

Insight into copper-cerium catalysts with different Cu valence states for CO-SCR and in-situ DRIFTS study on reaction mechanism - Jinfeng Li; Jiexuan Zhu; Shiying Fu; Lin Tao; Bingxian Chu; Qiuju Qin; Jingkai Wang; Bin Li; Lihui Dong (Fuel, 2023)

Fowl adenovirus serotype 4 52/55k protein triggers PKR degradation by ubiquitin–proteasome system to evade effective innate immunity - Qing He; Shaohua Lu; Yun Lin; Lihui Xu; Zhen Chen; Quanxi Wang (Veterinary Microbiology, 2023)

Zoning method of aquatic ecosystem functional management fourth-level region in the Daqing River Basin, China - Lihui Sun; Chang Shu; Lin Ding; Ziqiang Tian; Hao Liu (Journal of Environmental Management, 2023)

The toxicity of nano polyethylene terephthalate to mice: Intestinal obstruction, growth retardant, gut microbiota dysbiosis and lipid metabolism disorders - Xiaoying Lin; Hongxin Xie; Yanfei Zhang; Xue Tian; Liwei Cui; Nianqiu Shi; Liming Wang; Jiating Zhao; Lihui An; Jing Wang; Bai Li; Yu-Feng Li (Food and Chemical Toxicology, 2023)

Rapid identification of fish species by laser-induced breakdown spectroscopy and Raman spectroscopy coupled with machine learning methods - Lihui Ren; Ye Tian; Xiaoying Yang; Qi Wang; Leshan Wang; Xin Geng; Kaiqiang Wang; Zengfeng Du; Ying Li; Hong Lin (Food Chemistry, 2023)

Chromosomal mapping of a locus associated with adult-stage resistance to powdery mildew from Agropyron cristatum chromosome 6PL in wheat - Yida Lin; Shenghui Zhou; Xuezhong Liang; Baojin Guo; Bing Han; Haiming Han; Jingpeng Zhang; Yuqing Lu; Zhi Zhang; Xinming Yang; Xiuquan Li; Weihua Liu; et al. (Theoretical and Applied Genetics, 2022)

NOD1 inhibits proliferation and enhances response to chemotherapy via suppressing SRC-MAPK pathway in hepatocellular carcinoma - Xiaomin Ma; Yumin Qiu; Lihui Zhu; Yunxue Zhao; Yueke Lin; Dapeng Ma; Zhenzhi Qin; Caiyu Sun; Xuecheng Shen; Tao Li; Lihui Han (Journal of Molecular Medicine, 2020)

Variation of functional brain connectivity in epileptic seizures: an EEG analysis with cross-frequency phase synchronization - Haitao Yu; Lin Zhu; Lihui Cai; Jiang Wang; Chen Liu; Nan Shi; Jing Liu (Cognitive Neurodynamics, 2020)

Transcriptome analysis in different chieh-qua cultivars provides new insights into drought-stress response - Min Wang; Xiaoming He; Biao Jiang; Wenrui Liu; Yu’e Lin; Dasen Xie; Zhaojun Liang; Lihui Chen; Qingwu Peng (Plant Biotechnology Reports, 2019)

Development of InDel Markers for Identification of a Single Mendelian Locus Controlling Leaf Shape in Kenaf (Hibiscus cannabinus) - Liemei Zhang; Xuebei Wan; Lilan Zhang; Yi Xu; Jiantang Xu; Lihui Lin; Jianmin Qi; Liwu Zhang (Tropical Plant Biology, 2019)

Identification of Genes Involved in Flavonoid Biosynthesis of Chinese Narcissus (Narcissus tazetta L. var. chinensis) - Guiqing Wang; Biyun Yang; Jiacheng Wu; Peng Luo; Muhammad Anwar; Andrew C. Allan; Kui Lin-Wang; Richard V. Espley; Lihui Zeng (Plant Molecular Biology Reporter, 2018)

Molecular pathways involved in microRNA-mediated regulation of multidrug resistance - Rongrong Liao; Yuexia Lin; Lihui Zhu (Molecular Biology Reports, 2018)

Aeromonas veronii and aerolysin are important for the pathogenesis of motile aeromonad septicemia in cyprinid fish - Chao Ran; Chubin Qin; Mingxu Xie; Jinxiong Zhang; Jie Li; Yadong Xie; Yibing Wang; Shuning Li; Lihui Liu; Xiaozhe Fu; Qiang Lin; Ningqiu Li; et al. (Environmental Microbiology, 2018)
Summary Aeromonas species are ubiquitous inhabitants of freshwater environments, and are responsible for fish motile aeromonad septicemia (MAS). A. hydrophila is implicated as the primary etiologic agent of MAS. Here, we analysed MAS epidemiological data for cyprinid fish in southern China, and found that A. veronii infections dominated. Consistent with this observation, A. veronii isolates were generally more virulent than A. hydrophila isolates when infecting germ‐free zebrafish larvae via continuous immersion challenge. Through in vivo screening of the transposon library of the A. veronii strain Hm091, aerolysin was identified as the key virulence factor. Further results indicated that A. veronii Hm091 aerolysin disrupts the intestinal barrier of zebrafish, enabling systematic invasion by not only A. veronii Hm091 in a mono‐infection, but also A. hydrophila NJ‐1 in a mixed infection. Moreover, the differences in aerolysin expression and activity were the major contributor to the observed differences between the A. veronii and A. hydrophila strains regarding invasion efficacy via intestine. Together, our results provide new insights into the aetiology and pathogenesis of Aeromonas infections, and highlight the importance of A. veronii ‐targeted treatments in future efforts against MAS.

The biological features and genetic diversity of novel fish rhabdovirus isolates in China - Xiaozhe Fu; Qiang Lin; Hongru Liang; Lihui Liu; Zhibin Huang; Ningqiu Li; Jianguo Su (Archives of Virology, 2017)

Correlation between the germline methylation status in ERβ promoter and the risk in prostate cancer: a prospective study - Lihui Wang; Pan Zhang; Xiannan Meng; Xiang Chen; Zou Xiang; Xiaoqian Lin; Ye Liu; Weidong Gan; Xiaodong Han; Dongmei Li (Familial Cancer, 2016)

A prospective clinical study in hepatitis B e antigen-negative chronic hepatitis B patients with stringent cessation criteria for adefovir - Minghao Ha; Guotong Zhang; Shu Diao; Mingfang Lin; Liping Sun; Huiyuan She; Chenbao Kuan; Lihui Shen; Chunhong Huang; Wenjuan Shen; Zhongming Huang (Archives of Virology, 2012)

Genotype and host range analysis of infectious spleen and kidney necrosis virus (ISKNV) - Xiaozhe Fu; Ningqiu Li; Lihui Liu; Qiang Lin; Fang Wang; Yingtiao Lai; Haiming Jiang; Houjun Pan; Cunbin Shi; Shuqin Wu (Virus Genes, 2011)

Predicting miRNA’s target from primary structure by the nearest neighbor algorithm - Kao Lin; Ziliang Qian; Lin Lu; Lingyi Lu; Lihui Lai; Jieyi Gu; Zhenbing Zeng; Haipeng Li; Yudong Cai (Molecular Diversity, 2010)